2016
DOI: 10.1093/schbul/sbw038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism Associated Prefrontal Glutathione and Its Coupling With Brain Glutamate and Peripheral Redox Status in Early Psychosis

Abstract: GCLC high-risk genotypes are associated with low [GSHmPFC], highlighting that GCLC polymorphisms should be considered in pathology studies of cerebral GSH. Low brain GSH levels are related to low peripheral oxidation status in controls but with high oxidation status in patients, pointing to a dysregulated GSH homeostasis in early psychosis patients. GCLC polymorphisms and disease associated correlations between brain GSH and Glu levels may allow patients stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 61 publications
9
99
2
2
Order By: Relevance
“…Although GCLC GAG TNR polymorphism reportedly influences GSH levels in the European Caucasian population [78], we reported that specific genotypes may not have affected the levels in our study population (the group of North Americans that include African Americans) [79]. It remains elusive which genetic and/or environmental factors potentially influence the sulfo­raphane response in GSH levels.…”
Section: Discussionmentioning
confidence: 83%
“…Although GCLC GAG TNR polymorphism reportedly influences GSH levels in the European Caucasian population [78], we reported that specific genotypes may not have affected the levels in our study population (the group of North Americans that include African Americans) [79]. It remains elusive which genetic and/or environmental factors potentially influence the sulfo­raphane response in GSH levels.…”
Section: Discussionmentioning
confidence: 83%
“…Firstly, given the evidence that glutathione and glutamate levels in the brain are affected by a risk variant of the gene coding for the glutathione synthesis enzyme, the role of genetic influences should be investigated [22]. Secondly, although we controlled for current antipsychotic medication intake and metabolite concentrations, possible confounding effects of long-term medication use should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…One MRS study found reduced glutathione in the medial prefrontal cortex (mPFC) in schizophrenia patients compared with healthy controls [21]. Another recent study reported reduced glutathione only in schizophrenia patients carrying a risk variant of the gene coding for the ratelimiting enzyme in glutathione synthesis [22]. Four other studies reported no statistically significant differences in glutathione levels in the posterior medial frontal cortex [23], mPFC [24] or anterior cingulate cortex (ACC) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Unsuppressed water 1H MR spectra were used as an internal reference for the absolute quantification of metabolite concentrations. Tissue composition inside the MRS volume used for water content calculation and partial volume correction was calculated based on the segmentation of magnetization-prepared rapid gradientecho (MPRAGE) (Mugler and Brookeman 1990) images (TE/TR = 2.98/2300 ms, TI = 900 ms, flip angle = 9 degree, FOV = 240 × 256 mm2, matrix = 240 × 256, slice thickness = 1.2 mm) MPRAGE images using an in-house software (more details are reported elsewhere, Xin et al 2016). …”
Section: Spectral Quantificationmentioning
confidence: 99%